2013
DOI: 10.1016/j.stem.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Lamina Regulates Germline Stem Cell Niche Organization via Modulation of EGFR Signaling

Abstract: Summary Stem cell-niche interactions have been studied extensively with regard to cell polarity and extracellular signaling. Less is known about the way in which signals and polarity cues integrate with intracellular structures to ensure appropriate niche organization and function. Here we report that nuclear lamins function in the cyst stem cells (CySCs) of Drosophila testis to control the interaction of CySCs with the hub. This interaction is important for regulation of CySC differentiation and organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 58 publications
8
79
0
Order By: Relevance
“…Our findings reported here demonstrate that lamins are indeed not required for the self-renewal and differentiation of ESCs as judged by different in vitro differentiation models. This provides further support for a role of lamins in proper tissue building [10][11][12]. Our RNA-seq data indicates that ~600 genes do exhibit expression change upon lamin deletion.…”
supporting
confidence: 66%
“…Our findings reported here demonstrate that lamins are indeed not required for the self-renewal and differentiation of ESCs as judged by different in vitro differentiation models. This provides further support for a role of lamins in proper tissue building [10][11][12]. Our RNA-seq data indicates that ~600 genes do exhibit expression change upon lamin deletion.…”
supporting
confidence: 66%
“…Indeed, some important chromatin regulators and nuclear envelope proteins have been shown to undergo drastic changes in expression levels during normal spermatogenesis. Su(Hw), a multi-zinc finger DNA-binding protein that can function as a transcriptional insulator and modulator of chromatin association with the nuclear lamina (Soshnev et al, 2013;van Bemmel et al, 2010), and the PRC2 complex components E(z) and Su(z) (Chen et al, 2011) are strongly downregulated in early spermatocytes, whereas Lamin C (LamC) expression is induced (Chen et al, 2013). However, in these particular cases, we did not detect an abnormal expression program in dany mutant testis by immunolabeling (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the list of strongly derepressed genes in dany mutant testes contained a significantly higher number of genes strongly derepressed by Lam knockdown in the fat body (Chen et al, 2013) than expected stochastically (Table S1). For an initial evaluation of the effects of dany loss on intranuclear localization at the gene level by fluorescence in situ hybridization (FISH) to chromosomal DNA, inaC was selected as the gene most strongly derepressed in dany mutant testis according to our microarray data and as it is also associated with the nuclear lamina according to Lam-ID in Kc cells (Pickersgill et al, 2006), as well as strongly derepressed after Lam knockdown in fat body (Chen et al, 2013).…”
Section: Dany Is a Nuclear Protein That Associates With Chromatinmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed the finding that the Drosophila lamin-B is required for the testis development by regulating the EGF signaling in the cyst stem cells is aided by the knowledge that lamin-B interacts with some nucleoporins. 15 In addition to the developmental functions, the studies of human diseases caused by mutations in lamins have suggested that these proteins are required for the proper function of organs and tissues. For example, point mutations in lamin-A have been shown to cause a number of human diseases, including cardiomyopathy, muscular dystrophy, partial lypodystrophy, and a premature aging disease called progeria.…”
Section: Nuclear Lamins In Tissue Building and Maintenancementioning
confidence: 99%